“You have to walk on eggshells around him”: Female partners’ perspectives on the opportunities and challenges of dealing with a male partner’s depression—A qualitative study - Maja Stiawa; Paul Nickel; Gironimo Krieg; Katharina Senk; Reinhold Kilian; Natalie Lamp; Maria Panzirsch; Silvia Krumm (PLoS ONE, 2025)
Purpose Partners of people with mental illness can play an important role in helping them cope with the illness. Previous studies have highlighted the potential burden of depression on partners, but there has been little research into the perspective of female partners of men with depression in terms of their role and support needs. The aim of this study is to investigate the subjective view of female partners on the opportunities and challenges of dealing with a male partner’s depression. Materials and methods Qualitative semi-structured interviews were conducted online with 13 female partners of men with depression using a semi-structured interview guide. The transcripts were analyzed using qualitative content analysis. Results Four central categories were derived from the analysis: 1) perceived changes in depressed partners; 2) positive impacts on their relationship; 3) burdens and challenges in coping with the partner’s depression; and 4) experiences with and expectations of support. Female partners often take on an active and demanding role during the depression treatment period and exhibit a high level of caring behavior towards and responsibility for their partner with depression. Compensating for the impact of the partner’s depression on family life, women have to bear additional hardship that may lead to overload. The women’s needs are primarily met by close contacts from within their personal networks. Joint therapy sessions during the male partner’s treatment are valuable in helping cope with the illness together. Conclusions For partners of men with depression, the impact of the illness is ambivalent: On the one hand, the partner’s depression is associated with a number of difficulties and challenges. On the other hand, dealing with the illness together can also strengthen their relationship. Female partners of men treated for depression should be provided with low-threshold services, including therapeutic interventions that focus on successful joint coping.